Transformation of Female Masculinity in Bala Anjani Dance to Webtoon Comics as Gender Education Media - Nahdlatuzzainiyah, Nahdlatuzzainiyah; Sudewi, Ni Ketut Putri Nila; Putrajip, Mohamad Yudisa (Universitas Negeri Medan, 2024)
Bala Anjani Dance contains a message of gender equality, emphasizing that women and men have equal positions. This social message aims to eliminate gender discrimination and destroy negative stereotypes against women. However, the limitations of traditional art media limit the reach of this message. This study aims to transform masculinity in the choreography of the Bala Anjani Dance, which is full of social values, into a digital comic media based on the Webtoon platform to reach the wider community, especially the younger generation. The research method uses a qualitative-descriptive approach to analyze the art of the Bala Anjani Dance and a design approach to produce comic products. The media transfer process includes several stages: (1) ecranization to transfer the moral message of gender equality into a comic story; (2) reduction, namely simplifying the original story to make it more interesting; (3) additions and variations to the story, setting, and characterization; (4) product testing on 30 students; and (5) implementation, namely the creation of a digital comic to be published on Webtoon. The results of the study produced the character and story of the comic